Al Azhar Islamic High School 24 Boarding School's Leadership Style - Rahmanudin, Ii; Syah, Burhan Lukman; Afandi, Aqila Najiha Mohd (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
Leadership in an institution becomes a necessity so that the wheels of the institution system can be controlled properly. Especially boarding or dormitory-based institutions such as SMA Islam Al Azhar 24 Boarding School. Human resources who apply good leadership patterns also give birth to good systems. This research will discuss the leadership pattern applied at SMA Islam Al Azhar 24 Boarding School from several activities ranging from establishing the Al Azhar Santri Boarding Organization, Vocabulary Delivery, and Amaliyah Worship Activities. Researchers describe and analyze each activity at SMA Islam Al Azhar 24 Boarding School. The method used in this research is descriptive qualitative with a phenomenological approach. Researchers describe and analyze each existing activity. The results show that the leadership pattern at SMA Islam Al Azhar 24 Boarding School is perfect so boarding activities can run smoothly. The leadership pattern formed by the principal and teachers to Al Azhar students with a control system (guided, escorted, assigned with a spiritual approach to leadership, an idealistic approach, a humane approach, and a task approach and students can control boarding under the organization formed. Therefore, this leadership pattern can be applied to all institutions in overcoming the moral crisis in leadership.